2000
DOI: 10.1055/s-2000-9773
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Activity of Foeniculum vulgare and Crithmum maritimum Essential Oils

Abstract: The essential oils obtained from Crithmum maritimum L. (marine fennel) and two samples of Foeniculum vulgare Miller (common fennel) were analysed by GC and GC-MS and assayed for their antioxidant and antibacterial activities. The antioxidant activity of the oils was evaluated by two lipid model systems: a modified thiobarbituric acid reactive species (TBARS) assay and a spectrophotometric detection of hydroperoxydienes from linoleic acid in a micellar system. The oils demonstrated antioxidant capacities, compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
220
7
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(241 citation statements)
references
References 12 publications
6
220
7
8
Order By: Relevance
“…This lower sensitivity of Gram negative organisms has been related to the presence of an outer membrane surrounding their cell wall, which restricts the diffusion of hydrophobic compounds through its lipopolyssacharide covering (34). It has been reported that among Gram negative bacteria, P. aeruginosa appears to be least sensitive to essential oils (18,21,38). Therefore, this behavior was not observed in our study, because P. aeruginosa showed an MIC value similar to other Gram negative assayed bacteria, as well as did not develop smallest inhibition zones.…”
Section: Discussioncontrasting
confidence: 41%
“…This lower sensitivity of Gram negative organisms has been related to the presence of an outer membrane surrounding their cell wall, which restricts the diffusion of hydrophobic compounds through its lipopolyssacharide covering (34). It has been reported that among Gram negative bacteria, P. aeruginosa appears to be least sensitive to essential oils (18,21,38). Therefore, this behavior was not observed in our study, because P. aeruginosa showed an MIC value similar to other Gram negative assayed bacteria, as well as did not develop smallest inhibition zones.…”
Section: Discussioncontrasting
confidence: 41%
“…O óleo das folhas possui estragol, alfa-felandreno, limoneno e fenchona (Garcia et al, 2000). Dados farmacológicos: O óleo volátil apresenta ação antioxidante (Oktay et al, 2003;Ruberto et al, 2000), hepatoprotetora (Ozbek et al, 2003), espasmolítica (Amjad, 2000), antibacteriana (Daswani;Bohra, 2002;Ruberto et al;2000) e antifúngica (Ezzat, 2001). Extratos aquoso e etanólico dos frutos mostraram atividade antioxidante (Oktay et al, 2003), diurética (Beaux et al, 1997;Tanira et al, 1996), analgésica, antipirética (Tanira et al, 1996), colagoga e antibacteriana (Daswani;Bohra, 2002;Tanira et al, 1996), sem apresentar toxicidade ou efeito genotóxico, em camundongos (Shah et al, 1991).…”
Section: Foeniculum Vulgare Mill (Apiaceae) -Constituintes Químicosunclassified
“…The strain with the lowest susceptibility was P. aeruginosa (MIC=MBC=50 μl/ml). This strain is very resistant to most of the essential oils, owing to the hydrophilicity of its cell membrane surface [18][19][20][21]. Except for the strains K. pneumoniae and S. aureus, the oil had both inhibitory and bactericidal effect at the same concentration (MIC=MBC).…”
Section: Antimicrobial Activity Of S Hortensis Essential Oilmentioning
confidence: 99%